Neonatal inferior vena cava and renal venous thrombosis treated by thrombectomy and nephrectomy. Issue 11 (November 1985) - Clark, A G; Saunders, A; Bewick, M; Haycock, G; Chantler, C
Abstract : Neonatal inferior vena cava and renal venous thrombosis with obstruction was diagnosed clinically and confirmed by ultrasonography. Successful thrombectomy and nephrectomy were performed at 40 hours of age. Thrombus with obstruction occluding the inferior vena cava favours immediate surgery.